THE SIGNIFICANCE OF MUHAMMAD RIZA OGAHI'S TRANSLATIONS TODAY ("Conference on Universal Science Research 2023", 2023)
This article provides information about the work of the poet, historian and translator Muhammad Reza Ogahi, who lived in Khiva in the 19th century, creating works in various genres of literature. It is also about the description of Ogahi's works not only in poetic, but also in prose. It is analyzed that the poet pointed to the shortcomings of the political policy of that time and the good and bad qualities of people's character through his work.